Is er een mismatch tussen industrie en wetenschap in de Brusselse agglomeratie? Kennisoverdracht bij innoverende KMO's in kennisintensieve business services (KIBS) - Peter Teirlinck (Brussels Studies, 2017)
This study provides insights in knowledge spillovers in terms of the use of different sources of knowledge at the origin of innovation, collaboration in innovation, and the reliance on a closed or more open innovation strategy by firms in the Brussels agglomeration. The focus is on innovative small and medium-sized enterprises (SMEs) in knowledge intensive business services (KIBS) in Brussels. These firms are compared with their counterparts in the other large city agglomerations in Belgium. Based on data from two waves of the Community Innovation Survey (2008-2010 and 2010-2012) it is revealed that universities and public research organisations (PROs) play a rather limited role as providers of ideas at the origin of innovation in these firms in Brussels, and are significantly less solicited for industry-science collaboration. These findings contrast the more open innovation development strategy of SMEs in KIBS in the capital city agglomeration and the abundant presence of knowledge at universities and PROs, and hence raise the question of an industry-science mismatch.